2020
DOI: 10.1186/s12951-020-00604-7
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel-loaded solid lipid nanoparticles prevent tumor growth and lung metastasis of 4T1 murine mammary carcinoma cells

Abstract: Background: Metastasis causes the most breast cancer-related deaths in women. Here, we investigated the antitumor effect of solid lipid nanoparticles (SLN-DTX) when used in the treatment of metastatic breast tumors using 4T1-bearing BALB/c mice. Results: Solid lipid nanoparticles (SLNs) were produced using the high-energy method. Compritol 888 ATO was selected as the lipid matrix, and Pluronic F127 and Span 80 as the surfactants to stabilize nanoparticle dispersion. The particles had high stability for at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
79
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(91 citation statements)
references
References 70 publications
10
79
0
2
Order By: Relevance
“…2g and i, respectively). Adaptation to excessive ROS levels in cancer cells has been reported, suggesting they have a higher basal ROS level than normal cells (Kim et al 2019); therefore, treatments that elevate ROS levels break the redox homeostasis and causes cancer cell death, as we can see with MAGCIT-MB treatment (Rocha et al 2020). An antagonistic fact is, however, observed after treatment with free MB, in which toxicity levels were subjected to low rates of agents (Fig.…”
Section: Cell Viability Studiesmentioning
confidence: 84%
“…2g and i, respectively). Adaptation to excessive ROS levels in cancer cells has been reported, suggesting they have a higher basal ROS level than normal cells (Kim et al 2019); therefore, treatments that elevate ROS levels break the redox homeostasis and causes cancer cell death, as we can see with MAGCIT-MB treatment (Rocha et al 2020). An antagonistic fact is, however, observed after treatment with free MB, in which toxicity levels were subjected to low rates of agents (Fig.…”
Section: Cell Viability Studiesmentioning
confidence: 84%
“…The results of GSVA was in accordance with the GSEA results. Cell-cycle dysregulation is one of the hallmarks of cancer and several researches have reported that cell cycle disturbance is the most important mechanism for cancer occurrence and progression [65,66]. Given that the speci c function that novel four hub genes have in cell cycle regulation is unknown, additional research is required to investigate those mechanisms in breast cancer in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…[261] Docetaxel-loaded SLNs (DTX-SLNs) were investigated in metastatic breast tumors in vitro using murine breast adenocarcinoma (4T1), human breast cancer (MCF7), and murine embryo fibroblast (NIH-3T3) cells and in vivo using 4T1-bearing BALB/c mice. [262] It has been reported that DTX-SLNs induce apoptosis and microtubule damage, and decrease IL-6 production, B-cell lymphoma 2 (BCL-2) and Ki-67 expression, and tumor cell proliferation, leading to the inhibition of tumor progression and prevention of lung metastasis. [262] In another study, PTX-loaded SLNs modified with Tyr-3octreotide (TOC), a known ligand for somatostatin receptors overexpressed in glioma, were used for antiangiogenic and Reproduced with permission.…”
Section: Slnsmentioning
confidence: 99%
“…[262] It has been reported that DTX-SLNs induce apoptosis and microtubule damage, and decrease IL-6 production, B-cell lymphoma 2 (BCL-2) and Ki-67 expression, and tumor cell proliferation, leading to the inhibition of tumor progression and prevention of lung metastasis. [262] In another study, PTX-loaded SLNs modified with Tyr-3octreotide (TOC), a known ligand for somatostatin receptors overexpressed in glioma, were used for antiangiogenic and Reproduced with permission. [264] Copyright 2019, The Royal Society of Chemistry.…”
Section: Slnsmentioning
confidence: 99%